Effectiveness of virtual & augmented reality learning environments in enhancing students' self-efficacy - Chan, Ming Yi (Nanyang Technological University, 2023)
This paper presents the results of an experimental study of the effects of Virtual Reality & Augmented Reality (VAR) learning environments on students’ academic performance and self-efficacy (SE). In the study, SE was measured across three dimensions, course-specific SE, content-specific SE, and problem-specific SE. VAR simulations were used to teach engineering students about engineering applications, helping learners grasp abstract engineering concepts and gain hands-on experience. Quantitative data on students’ academic performance and SE were collected using Likert questionnaires administered before and after the VAR teaching activities. Focus group discussions were conducted as a qualitative approach to gain an in-depth understanding of student’s overall learning experience in the VAR environment. The results have shown that VAR learning activities had a positive effect on students’ academic performance and SE. Across the three SE dimensions, problem-specific SE had the greatest improvement. The implications of the results are then discussed for further research in the field of the application of VAR in education.